Evaluation of Intra-Uterine Lugol's Iodine Therapy and Double PGF2α Shot for Treatment of Subclinical Endometritis in Dairy Cattle - Gupta, Chhavi; Prabaharan, V; Thangamani, A; Sabarinathan, A; Mervin Kennady, R V (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
This study was performed to diagnose subclinical endometritis in the field and to evaluate and compare the reproductive performance of repeat breeding dairy cows treated with intrauterine Lugol’s iodine (1%) and double PGF2α therapy. Two hundred eighty-six repeat breeding dairy cows brought to Veterinary Clinical Complex of the College, Tirunelveli during the period 2018-2022 were screened for subclinical endometritis with Whiteside test (positive) & polymorphnucleus (PMN) cells % (>5%), which revealed 20.98 % (60/286) incidence of subclinical endometritis (SCE). These 60 SCE positive animals were randomly divided into 3 equal groups. Group 1 (n=20) was subjected to sexual rest for one cycle, Group 2 (n=20) was treated with intrauterine Lugol's iodine (1%) therapy for three consecutive days and Group 3 (n=20) was treated with an injection Cloprostenol sodium 500 µg i/m twice on day 7 and day 18 post-estrus. The reduction in PMN % was highly significant (p
Keywords: Conception rate; Dairy cattle; Double PGF2α shot; Lugol’s iodine; PMN cells; Sexual rest; Subclinical endometritis